2010
DOI: 10.1152/ajplung.00431.2009
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A phosphorylation of tau-serine 214 reorganizes microtubules and disrupts the endothelial cell barrier

Abstract: compartmentalized to near membrane domains in endothelium, where it strengthens endothelial cell barrier function. Phosphodiesterase 4D4 (PDE4D4) interacts with the spectrin membrane skeleton and prevents cAMP from accessing microtubules. Expression of a dominant-negative PDE4D4 peptide enables cAMP to access microtubules, where it results in phosphorylation of the nonneuronal microtubule-associated protein tau at serine 214. Presently, we sought to determine whether PKA is responsible for tau-Ser214 phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…In future studies it will be imperative to clone and sequence the endothelial Tau. (25,46,47). We found that the increased levels of cAMP and cGMP that paralleled gap formation in P. aeruginosa ExoY ϩ -infected pulmonary microvascular endothelial cells resulted in increased Tau Ser-214 phosphorylation, whereas cells infected with P. aeruginosa ExoY K81M did not display increased Tau Ser-214 phosphorylation (Fig.…”
Section: Two Isoforms Of Tau Are Detected In Pulmonary Microvascular mentioning
confidence: 70%
See 1 more Smart Citation
“…In future studies it will be imperative to clone and sequence the endothelial Tau. (25,46,47). We found that the increased levels of cAMP and cGMP that paralleled gap formation in P. aeruginosa ExoY ϩ -infected pulmonary microvascular endothelial cells resulted in increased Tau Ser-214 phosphorylation, whereas cells infected with P. aeruginosa ExoY K81M did not display increased Tau Ser-214 phosphorylation (Fig.…”
Section: Two Isoforms Of Tau Are Detected In Pulmonary Microvascular mentioning
confidence: 70%
“…Previous studies from our group (25,46,47) and others (48) have resolved that Tau or a Tau-like protein is expressed in pulmonary microvascular endothelial cells. It is not clear, however, whether endothelial Tau is similar to those Tau isoforms found in the central nervous system.…”
Section: Two Isoforms Of Tau Are Detected In Pulmonary Microvascular mentioning
confidence: 89%
“…In addition, membrane-associated cAMP protects endothelial barrier function by activating the exchange protein directly activated by cAMP (EPAC), which forms a ternary complex with PKA and PDE4D4 and subsequently stabilizes VE-cadherin-based adherens junctions (84). However, if PDE4D4 is inhibited, cAMP diffuses into the cytosol and activates cytosolyic PKA, which initiates a reorganization of the microtubules through phosphorylation of tau-Ser 214 , generating intercellular gaps that increase endothelial permeability (85). Additional studies will be needed to determine whether these or alternative mechanisms are responsible for the uPA-PAI-1-induced PKA-dependent increase in PMV permeability that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these effects were analogous to the barrier-disruptive effects of soluble ExoY or sACI/II adenylyl cyclase activity. When tau serine 214 is mutated to alanine, loss of phosphodiesterase D4D activity failed to reorganize microtubules and disrupt the barrier (179). Thus, in pulmonary endothelium, phosphodiesterase 4D4 localizes to the subplasma membrane space to spatially limit migration of the cAMP signal into the cytosol.…”
Section: Bacterial Soluble Adenylyl Cyclases Disrupt the Endothelial mentioning
confidence: 99%
“…Thus, in pulmonary endothelium, phosphodiesterase 4D4 localizes to the subplasma membrane space to spatially limit migration of the cAMP signal into the cytosol. Furthermore, cytosolic cAMP leads to phosphorylation of tau and decreased endothelial barrier integrity (30,179).…”
Section: Bacterial Soluble Adenylyl Cyclases Disrupt the Endothelial mentioning
confidence: 99%